2003
DOI: 10.1152/ajpgi.00463.2002
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of TNBS-induced colon inflammation in rats by phospholipase A2 inhibitor

Abstract: The pathophysiology of inflammatory bowel disease (IBD) involves the production of diverse lipid mediators, namely eicosanoids, lysophospholipids, and platelet-activating factor, in which phospholipase A2 (PLA2) is the key enzyme. Accordingly, it has been postulated that control of lipid mediator production by inhibition of PLA2 would be useful for the treatment of IBD. This hypothesis was tested in the present study by examining the therapeutic effect of a novel extracellular PLA2 inhibitor (ExPLI), composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Thus high expression of Pla2g2a in colitis-susceptible C3 mice might contribute to IBD susceptibility because of harmful effects of the enzyme products on the mucosa. This is corroborated by a recent study, in which experimental IBD was ameliorated by an extracellular phospholipase A2 inhibitor (28). The human homolog is located near a susceptibility locus for human IBD (IBD7).…”
Section: Discussionsupporting
confidence: 73%
“…Thus high expression of Pla2g2a in colitis-susceptible C3 mice might contribute to IBD susceptibility because of harmful effects of the enzyme products on the mucosa. This is corroborated by a recent study, in which experimental IBD was ameliorated by an extracellular phospholipase A2 inhibitor (28). The human homolog is located near a susceptibility locus for human IBD (IBD7).…”
Section: Discussionsupporting
confidence: 73%
“…These kind of lipid conjugates have been shown to protect membranes from diverse types of sPLA 2 s 29 30 and ameliorate different sPLA 2 related inflammatory conditions including endotoxin induced sepsis in rats, 24 allergic experimental encephalomyelitis in rats and mice, 23 and TNBS induced colitis in rats. 31 We have previously shown that sensitisation of rats with OVA is associated with an increase in sPLA 2 and CysLT production together with suppression of cPLA 2 and PGE 2 production. These processes were reversed by systemic (subcutaneous) treatment with the cell impermeable PLA 2 inhibitor HyPE which also suppressed the early response (bronchoconstriction) to challenge with OVA.…”
Section: Discussionmentioning
confidence: 93%
“…cPLA2 activity was determined by the hydrolysis of radioactively labeled lipid membranes (liposomes) containing AA-carrying PL, as previously described (20).…”
Section: Methodsmentioning
confidence: 99%
“…The ExPLIs, designed and synthesized in the laboratory of S. Yedgar (42), have been previously found effective in amelioration of inflammatory processes in cell cultures and in animal models. These include inhibition of lipid membrane hydrolysis by diverse types of sPLA 2 (9), inhibition of group V sPLA 2 activation in LPS-stimulated P388D macrophages (3), endotoxin-induced sepsis in rats, as expressed by reduced mortality rate, blood cytokine level (TNF-␣, IL-6), and expression of type IIA sPLA 2 and inducible nitric oxide synthase in liver and kidney of septic rats (4), suppression of sPLA 2 and PGE 2 production by LPS-stimulated cultured rat brain glial cells and experimental allergic encephalomyelitis in rats and mice (29), and trinitrobenzensulfonic acid-induced colitis in rats, expressed by reduced mortality rate, histology, and blood sPLA 2 activity (20). Using the ExPLIs, in the present study we have found that OVA-induced asthma in rats is associated with elevation of sPLA 2 and suppression of cPLA 2 activity and expression in the lung.…”
mentioning
confidence: 99%